On Innovating: An interview with Gautam Ahuja - Arzi Adbi; Andrea Contigiani; Gabriel Szulanski; Gautam Ahuja (Journal of Organization Design, 2020)
At the 2016 SMS Foundations Session interview with Professor Gautam Ahuja, we explored the key insights of his research trajectory, with a special focus on how organizations successfully innovate. We discussed the major ideas, theories, and results that he and his co-authors generated throughout his successful career. The interview was conducted on September 18, 2016 at the Strategic Management Society Annual Conference in Berlin, Germany. This article discusses Gautam's role in the organizations' literature, reports excerpts of the interview, and concludes with a postscript from Gautam Ahuja written for the community of organization design scholars.
Keywords: 650; Innovation; Organizations; Strategy; Firm boundaries; Inter-firm relationships; Networks; Acquisitions